Evaluation Model of Sustainable Development Planning in Regional Policy Implementation and Local Government Administration - Nasution, Muhammad Arifin; Ginting, Wiro Oktavius; Revida, Erika; Trimurni, Februati (Journal of Ecohumanism, 2025)
Evaluation Model of Sustainable Development Planning in Regional Policy Implementation and Local Government Administration. This study's primary focus is the significant discrepancy between the planning and execution of development initiatives in the fields of education, health, and the environment. The method used was a descriptive qualitative approach with data collection through observation, in-depth interviews, and Focus Group Discussions (FGDs) with various stakeholders, including government officials and community leaders. The results showed that low inter-organization Regional Apparatus (OPD) coordination and minimal community participation hindered the success of development programs. Furthermore, performance metrics are not achieved evenly due to a mismatch between the budgeting and planning documents. This study suggests a more flexible and empirically supported strategy for evaluating development planning incorporating improved data management, community involvement in Musrenbang, and OPD performance analysis. The establishment of a Regional Development Evaluation Team (TEPD) is also recommended to conduct periodic evaluations. It is expected that with the application of this model, the effectiveness of development in Dairi Regency can increase, and support the achievement of sustainable development goals optimally.